Cause Analysis of Cutting Process Problems on The Size of Nata De Coco Cutting Type NDC 12 - Ghani, Aria Azizah Ahmad; Rahmadhia, Safinta Nurindra (Universitas Ahmad Dahlan, 2021)
The nata de coco cutting process takes place using three types of cutting machines, namely conventional cutting machines, conveyor cutting machines, and chain conveyor machines. The process of cutting nata often experiences practical problems, especially on the size of the pieces that do not match the predetermined criteria. This results in a decline in product quality and customer acceptance. The purpose of this study was to determine the causes of problems in the process of cutting nata de coco type NDC 12. Problem analysis was carried out using quantitative methods presented in the table of oversize nata de coco test data on each machine used so that deviations in the size of the nata produced against the criteria had been determined. determined, as well as qualitative methods with fishbone diagrams based on data from observations, interviews and documentation. The results of the size of the NDC 12 nata de coco pieces in general are still not in accordance with the standards set by the company, it can be seen from the average value of the largest defect in the chain conveyor machine, which is 12.75g pre-sorting treatment and 7.17g post-treatment. sort. This is largely due to machine work that is less than optimal and the pre-cutting process is not in accordance with work procedures.